Analisis penerapan akuntansi manajemen lingkungan pada UD. SUMU di Manado - Toding, Fritz Gerald; Alexander , Stanly W.; Tirayoh, Victorina Z. (Yayasan Widyantara Nawasena Raharja, 2024)
This study aims to determine the application of environmental management accounting of the UD. Sumu in Manado. The research method used in this research is descriptive qualitative. The results of the research obtained Environmental costs related to waste management are costs that arise from activities related to the management of production waste to prevent environmental pollution. Waste management plays a crucial role in company operations. UD. Sumu has carried out the accounting process for waste management costs. Although UD. Sumu has recorded environmental costs by allocating funds for waste handling, but the reporting of these costs still does not meet the applicable standards. The company, in carrying out its operations, is committed to not producing negative impacts on the environment. So far, UD. Sumu has not specifically recorded its environmental activities as part of environmental costs, especially prevention costs.